Kebijakan Hukum Pidana Dalam Mengimplementasikan, Nilai Keadilan, Dan Kepastian Hukum (Studi Kasus Pencemaran Nama Baik). - Hafidz Jawad; Khalid Arham (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
Micro, Small and Medium Enterprises (MSMEs) are one of the key sectors for the City of Surakarta, reflected in the growth in terms of the number of business units. Until 2020, there were 1,235 small and medium business units in Surakarta City, as well as 164 creative businesses and 6,010 non-formal businesses that have the potential to include micro-level business actors. The existence of UMKM in Surakarta City has a better number than other urban-characterized areas in the Central Java region (Padwangi, 2019). The Central Bureau of Statistics for the City of Surakarta notes that by 2020 there are 275 medium businesses, 960 small businesses, and 6174 creative and non-formal businesses where micro businesses have the potential to be included. The number of business units increased by 0.14% compared to 2019, and this growth rate is in the good category when referring to the 2020 Regional Competitiveness Index.